Museu de Arte do Rio-MAR : reflexões sobre museu, arte contemporânea e cidade - Souza, Angela Gomes de (2015)
The present study provides reflections on museum themes, contemporary art and city made from the study of the Rio Art Museum - MAR and it is subdivided into three analysis axis. The first axis, "MAR and the Center of Rio de Janeiro", points out issues reg